Study on housing defect in Malaysia - Nor Hidayu, Norazham (2017)
The building defects are common issue associated with housing in Malaysia. Common type of building defect include structural defect such as crack or collapse, defective of electrical wiring or lighting, defective of plumbing, drainage system, cooling or heating system, sound proofing and also fire protection system. Damage caused by land movement or earth settlement are also can causes building defect. This research objective is to identify the common types of building defect, identify the causes of building defect and also analyse the building defect occur in housing. Based on a combination of literature review and questionnaire surveys, this paper explores the factors of the building defect occur and possible reducing method to minimize the problem, and also the relationship between measures identified with the factors. A quantitative research was conducted by sending 50 sets of questionnaire to the respondents. The results from 50 sets of completed questionnaire were used for the quantitative analysis. In this research shown that the highest ranked for the building defects was paint peeling. Then, poor functioning of system in housing, dampness on basements, beams, column and slab also always occur in housing. The most significant factor of building defect in housing is building not proper inspection maintenance. In conclusion, this problem would be important and should minimize the building defects by knowing the common solution when building defect occur immediately.